The role of early cortisol level in the assessment of the radicality of resection in central Cushing's disease - Masopust, Václav; Netuka, David; Hořínek, Daniel; Kosák, Mikuláš; Hana, Vaclav; Kršek, Michal (Neuro-endocrinology letters, 2016)
INTRODUCTION: To increase radicality and avoid surgical complications new treatment options are under investigation. One of the promising possibilities is to assess early morning cortisol levels on the first and second postoperative day. MATERIAL AND METHODS: We enrolled 34 patients (9 males, 25 females) diagnosed with Cushing's disease. Blood samples to determine cortisol level were taken always at 06:00 and sent to the lab. The samples were taken on the first and second postoperative day. For all patients, standard four-handed, a bi-nostril endoscopic endonasal technique was used. Endocrinological follow-up (6-34 months) was performed using morning cortisol sampling. RESULTS: In total, 36 patients (88%) were disease-free post-surgery. In the group with early postoperative levels of morning cortisol of less than 463 nmol/L, only 2 of 29 patients (7%) exceeded the final morning level of cortisol at follow-up. In patients with early postoperative cortisol levels between 17 nmol/l and 234 nmol/l all subjects showed normal postoperative cortisol levels. DISCUSSION: In 30 of 34 patients (88%), the level of cortisol was within normal limits. The prediction importance of early measurement of cortisol is 93% for patients with early postoperative cortisol levels of less than 463 nmol/L. The prediction importance of early measurement of cortisol is 100% for patients with early postoperative cortisol levels from 17 to 234 nmol/L. CONCLUSION: The monitoring of early morning cortisol levels seems to be an important tool in the management of central Cushing's disease.
Keywords: senioři; hypofýza; Pituitary Gland; endoskopie; pooperační období; Postoperative Period; mladiství; výsledek terapie; Middle Aged; mužské pohlaví; Adult; mladý dospělý; neurochirurgické výkony; Monitoring, Physiologic; Postoperative Complications; dítě; Follow-Up Studies; hydrokortison; hypersekrece ACTH v hypofýze; Child; Endoscopy; následné studie; Young Adult; ženské pohlaví; Hydrocortisone; Humans; Pituitary ACTH Hypersecretion; lidé středního věku; dospělí; monitorování fyziologických funkcí; Neurosurgical Procedures; Female; Aged; Adolescent; Treatment Outcome; pooperační komplikace; lidé; Male